GENETIC DIAGNOSIS AND REPRODUCTIVE BIOLOGY OF INTRODUCED MYSTACOLEUCUS MARGINATUS IN THE TOBA LAKE, NORTH SUMATRA - Siswanta Kaban; Arif Wibowo (Indonesian Fisheries Research Journal, 2018)
After M. marginatus has been introduced to Toba Lake, North Sumatra, the status of M.marginatus stocks and their biological properties is unknown. In this study, we examine the genetic patterns of the M. marginatus in Toba Lake, North Sumatra Province. Employing the cytochrome c oxidase subunit I (COI) gene of the mtDNA, we profile the genetic variation within M. marginatus in Toba Lake. We also analyzed reproductive characteristic and commercial catches of M. marginatus. The result shown M. marginatus is a synonim for M. marginatus, in total, 1 polymorphic sites (represent singleton dimensions) was identified and phylogenetic reconstruction reveal low levels of genetic diversity with no clear pattern of haplotype-partitioning. Nucleotide diversity analysis infer the present of two lineages. The Ne value of M. marginatus (1,936 to 3,878), the population has not experienced population growth/expansion as expected and the total production of M. marginatus in Toba Lakeof the year for 2013 has ranged between 3,347.05 – 6,694.1 ton. M. marginatus in the Toba Lake share similar life history traits include maximum body size, longevity, age at maturity, and fecundity(the number of eggs produced). M. marginatus is categorized as the opportunistic strategy consisted of fishes with short generation time, low batch fecundity, and low investment per offspring. This lifehistory traits approach of M. marginatus are important for guide fisheries management for its sustainability. More over the information can be use as pilot data and apply it to data-poor species.